Effective use of biochar as an additive for alkali-activated slag mortar production. (17th March 2023) - Egodagamage, Harshani; Yapa, H.D.; Samith Buddika, H.A.D.; Navaratnam, Satheeskumar; Nguyen, Kate
Highlights: Rice husk biochar is used as a green supplement to produce alkali-activated slag. Biochar increases the compressive strength of alkali-activated slag except at 1-day. Biochar promotes the formation of hydration products. Abstract: This research aimed at assessing the feasibility of activating biochar and ground granulated blast furnace slag (GGBS) combination using a blend of sodium carbonate and sodium hydroxide as the alkaline activator as a potential sustainable construction material. Taguchi Orthogonal experimental design was used to optimise the mix proportions considering three distinct biochar types (Rice husk biochar- (RB) and two sewage sludge biochar types), three biochar replacement levels (1, 2 and 5%) and three Na2 O contents (6, 8 and 10%) as the parameters. The effect of biochar on the compressive strength, flowability and setting time was tested. The hydration mechanisms of biochar supplemented alkali-activated slag (AAS) were studied by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and 29 Si nuclear magnetic resonance (NMR). In view of the overall performance in compressive strength, flow and setting time, the use of 2% RB with 10% Na2 O content was identified to be the optimum combination. In contrast to the control mix, the optimum mix showed increment of compressive strength at 3-, 7-, 28- and 56-days of 16.5%, 13.5%, 7.4% and 12.2% respectively. Hydration analyses revealed that RB enhanced the formation of hydration products. Such improvements to the AAS product has potentially been introduced by the biochar's high-water absorption and retention property.